2019
DOI: 10.14745/ccdr.v45i23a02
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the rising rates of gonorrhea and drug-resistant gonorrhea: There is no time like the present

Abstract: Increasing rates of gonococcal (GC) infection and antimicrobial resistant (AMR) GC, are a serious public health concern for Canada and around the world. Previously recommended treatments are ineffective against many of the gonorrhea strains circulating today. The current recommendation for combination therapy is now being threatened by globally emerging and increasingly resistant strains. It is important that coordinated efforts be made now to ensure these new global strains do not become established in Canada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…After implementing antimicrobial stewardship programs in the emergency department, a markedly reduced number of unnecessary antimicrobial prescriptions (25.6% before the program vs. 17.4% after the program) were found in the outpatient [8]. Such improper clinical use of antimicrobial agents resulted in increased resistance with higher numbers of deaths from treatable and curable infections before the emergence of resistance [9,10]. For example, the conventional treatment for the sexually transmitted disease gonorrhea is azithromycin and ceftriaxone.…”
Section: Implementation Of Antimicrobial Stewardship To Reduce Antimimentioning
confidence: 99%
“…After implementing antimicrobial stewardship programs in the emergency department, a markedly reduced number of unnecessary antimicrobial prescriptions (25.6% before the program vs. 17.4% after the program) were found in the outpatient [8]. Such improper clinical use of antimicrobial agents resulted in increased resistance with higher numbers of deaths from treatable and curable infections before the emergence of resistance [9,10]. For example, the conventional treatment for the sexually transmitted disease gonorrhea is azithromycin and ceftriaxone.…”
Section: Implementation Of Antimicrobial Stewardship To Reduce Antimimentioning
confidence: 99%
“…In a similar line of observation, the Centers for Disease Control and Prevention (CDC) reported that during 2010–2011, around 154 million times, antibiotics were prescribed in the ambulatory care settings in the U.S., of which ~47 million were estimated as unnecessary or inappropriate prescriptions ( 6 ). Such an irrational use of antimicrobial drugs partly contributed to the development of resistance against the microorganisms, once treatable before the emergence of resistance ( 7 , 8 ). One unfortunate example would be the treatment of gonorrhea.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, ertapenem has rapidly emerged as a gonorrhea treatment due to multidrug-resistant gonorrhea [ 14 , 15 ]. However, gonorrheal treatment failure with dual antimicrobial therapy (ceftriaxone combined with azithromycin or doxycycline) has been confirmed worldwide, as well [ 16 , 17 , 18 , 19 , 20 ]. Thus, the limited treatment options and the spread of hyper-variant ceftriaxone and azithromycin-resistant N. gonorrhoeae strains are significant public health concerns.…”
Section: Introductionmentioning
confidence: 99%